A snapshot of personalized medicine in palliative care (UCC Student Medical Journal, 2024)
Palliative care is an interdisciplinary care system that addresses the physical, emotional, social, and spiritual needs of patients and their families facing serious illness. It includes a team of medical professionals who work together to improve patient overall quality of life. While almost half of those who die in the US receive hospice services, many hesitate to enrol early due to the requirement to forgo curative treatment. To meet this challenge, unlike hospice care which may require forgoing curative treatment, palliative care services can be provided alongside curative treatments. When disease-modifying treatments are no longer an option, the traditional roles of medical team members change, with palliative medicine experts taking on a larger role in patient care. This comprehensive care can include managing pain and symptoms, providing social services and counselling, and assisting with daily living activities and spiritual support, among other services. Overall, palliative care services aim to enhance existing care services and involve additional support from family and community groups.
Keywords: Medical Ethics; Ethical Discussion; personalized medicine